Cystic fibrosis transmembrane conductance regulator function in patients with chronic pancreatitis. Issue 8 (25th February 2022) - Schlosser, Tobias; Fischer, Daniel; Büttner, Sandra; Blank, Valentin; Hoffmeister, Albrecht
Abstract: Background: Pathogenesis of chronic pancreatitis (CP) is still not entirely understood with many patients probably having more than 1 underlying etiology. Besides toxic-metabolic factors, genetics contribute to disease development. Mutations in cystic fibrosis transmembrane conductance regulator ( CFTR ) are shown to increase risk for CP. Activity of CFTR can easily be accessed in vivo by measurement of nasal potential difference (PD). Methods: We compared in this monocentric study 17 CP patients from the outpatient unit of our university hospital with 30 healthy controls regarding nasal PDs by using a superfusion protocol. Additionally, demographic and lifestyle data of all persons were recorded. Results: Seventeen patients (12% female, median age 48 years) with CP and 30 healthy volunteers (47% female, 25 years) were included in the study. Patients with CP had a significant higher proportion of CFTR dysfunction ( P = .04). Furthermore, demographics differed between the 2 groups with CP patients being older ( P < .001). There were differences in daily alcohol consumption ( P = .001) and smoking habits (smokers vs nonsmokers: P = .01, pack years: P = .002). Conclusions: PD measurement is an easily accessible way to show CFTR dysfunction as an etiological factor of CP. Cigarette smoking might impair CFTR function and therefore be 1 preventable cause of CP evolution.